Marketing Mix in Self-help Libraries: An Analytic Study - Koko Srimulyo, Nico Rizky Sukma, (Opción, 2020)
The identification of users’ needs is based on the developments of information technology and science that occur in society. This research aims to know the implementation of marketing mix elements. The variables examined in this study are product, price, promotion and place. Data was collected by distributing questionnaires to respondents. Overall, the four variables scored high, which means that the variables and factors that support marketing efforts have a positive and useful impact on library users. However, there are still some indicators that have low value, such as prices that has not meet the users’ expectations.